Nexus Between Coronavirus Epidemic and Educational Industry: Scenario of Online Teaching Strategies - Leung , Chi Hong (Asian Journal of Empirical Research, 2020)
During the global suspension of face-to-face classes due to the coronavirus epidemic, conducting online teaching becomes an essential part of offering the best learning experience to students for this difficult period. This paper suggests various online teaching and learning tactics in the epidemic. A survey was performed to collect quantitative feedback from 430 university students taking business subjects with the implementation of the suggested teaching and learning activities. Moreover, 40 students were interviewed to collect qualitative feedback on online teaching practices in other courses that they experienced. The major findings are that students were concerned about the quality of online learning materials, the interaction between students and teachers, technical issues (e.g., the stability of network connection), and accessibility of online platforms, learning materials, and their user-friendliness. In addition, it is found that i) students should be able to access communicative support and delivered content remotely, ii) teachers should be supported in adaptation to online teaching, and iii) technological resources should be utilized to sustain online and remote teaching and learning.